Evaluation of prolyl oligopeptidase and acetylcholinesterase inhibition by Phyllanthus tenellus Roxb. from Brazil. Issue 11 (3rd June 2021) - dos Santos, Maura Z.; de Ávila, Janaína; Morel, Ademir; Canto-Dorow, Thais S.; Mostardeiro, Marco A.; Dalcol, Ionara I.
Abstract: Phyllanthus tenellus Roxb. (Phyllanthaceae) is a plant used in Brazilian folk medicine for the treatment of intestinal infections and diabetes. Despite its use in traditional medicine, it was reported that P. tenellus extract may cause several effects in the central nervous system (CNS) of animals, such as agitation and signs of depression. The aim of this study was to determine the main constituents of P. tenellus methanol extract and to investigate whether the extract is able to inhibit the enzymes prolyl oligopeptidase (POP), acetylcholinesterase (AChE) and dipeptidyl peptidase-IV (DPP-IV). Corilagin (1 ) was isolated as the main constituent of the P. tenellus extract, along with rutin (2 ) and vitexin-2″- O -rhamnoside (3 ). The extract presented the ability to inhibit mainly POP. Dichloromethane and ethyl acetate fractions showed the highest inhibitory potency against POP (IC50 values of 1.7 ± 0.4 and 11.7 ± 2 µg/mL, respectively). All fractions were inactive against AChE. Corilagin displayed selective POP inhibition in a dose-dependent manner, with IC50 = 19.7 ± 2.6 µg/mL. Corilagin exhibited moderate capacity to pass through the phospholipid membrane by passive diffusion, presenting effective permeability (Pe) of 1.26 × 10 –7  cm/s. Abstract : UF0001